Copper- and ligand-free sonogashira reaction catalyzed by Pd(0) nanoparticles at ambient conditions under ultrasound irradiation - Gholap, Atul R.; Venkatesan, K.; Pasricha, R.; Daniel, Thomas; Lahoti, Rajgopal J.; Srinivasan, K. V. (Journal of Organic Chemistry, 2005)
The Sonogashira reaction proceeds at ambient temperature (30 degrees C) in acetone or room-temperature ionic liquid, 1,3-di-n-butylimidazolium tetrafluoroborate ([bbim]BF4), as solvent under ultrasound irradiation to give enhanced reaction rates, excellent chemoselectivity, and high yields in the absence of a copper cocatalyst and a phosphine ligand. TEM analysis showed the formation of stable, crystalline, and polydispersed Pd(0) nanoparticles as catalyst for the reaction.

Copper-, ligand- and solvent-free synthesis of ynones by coupling acid chlorides with terminal alkynes - Palimkar, Sanjay S.; Kumar, P. Harish; Jogdand, Nivrutti R.; Daniel, Thomas; Lahoti, Rajgopal J.; Srinivasan, Kumar V. (Tetrahedron Letters, 2006)
A general and efficient copper-, ligand- and solvent-free synthesis of ynones by coupling of a wide range of acid chlorides with terminal alkynes catalyzed by palladium(II) acetate at room temperature is reported. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: ligandless; neat; ynones

Convenient and efficient protocol for the synthesis of acylals catalyzed by bronsted acidic ionic liquids under ultrasonic irradiation - Borikar, Sanjay P.; Daniel, Thomas (Ultrasonics Sonochemistry, 2011)
The synthesis of acylals (1,1-diacetates) via the reactions of aldehydes with acetic anhydride was carried Out in 85-97% yields at room temperature under ultrasound irradiation catalyzed by the Bronsted acidic ionic liquid [bmpy]HSO(4). This method provides several advantages, such as solvent-free conditions, operational simplicity, higher yields, and reduced environmental consequences. The ionic liquid was recovered and reused. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: 1; 1-Butyl-3-methylpyridinium hydrogen sulfate; 1-Diacetates; Acylals; Ionic liquid; Solvent-free; Ultrasonic irradiation